2022
DOI: 10.1186/s12940-022-00841-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-level plasticizer exposure and all-cause and cardiovascular disease mortality in the general population

Abstract: Background Plasticizers, also called phthalates, are a group of chemicals widely used in daily life. A previous report showed no significant association between phthalate metabolite concentrations and mortality. We investigated the association of urinary phthalate levels and individual phthalate metabolite levels with all-cause and cardiovascular disease (CVD) mortality after standardizing the phthalate concentration. Methods A total of 6,625 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…In a recent study by Trasande et al from 2022, a positive association between MEP and cardiovascular mortality was observed, but no further significant associations between individual phthalate metabolites and mortality risks (Trasande et al, 2021). In a similar study by Zeng et al from 2022(Zeng et al, 2022, the strongest association was between MBzP and all-cause mortality risk, which is in line with our study. Zeng et al further reported a significant positive association between MECPP levels and CVD mortality, while cancer mortality was not investigated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent study by Trasande et al from 2022, a positive association between MEP and cardiovascular mortality was observed, but no further significant associations between individual phthalate metabolites and mortality risks (Trasande et al, 2021). In a similar study by Zeng et al from 2022(Zeng et al, 2022, the strongest association was between MBzP and all-cause mortality risk, which is in line with our study. Zeng et al further reported a significant positive association between MECPP levels and CVD mortality, while cancer mortality was not investigated.…”
Section: Discussionsupporting
confidence: 92%
“…NHANES is an open resource that is available to researchers worldwide, and three previous analyses on phthalates and mortality risks have been carried out based on data from the study (Sturgeon et al, 2016;Trasande et al, 2021;Zeng et al, 2022). An earlier analysis by Sturgeon et al from 2016 did not provide evidence for associations between urinary phthalate levels and cardiovascular mortality risk (Sturgeon et al, 2016), while all-cause and cancer mortality were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the US government and some states have set guidelines regulating DEHP levels in air, water, and consumer products, human exposure to this chemical is still widespread [25]. Both Pb and DEHP exposure are associated with numerous adverse cardiovascular outcomes in human population studies, including congenital heart defects, heart failure, hypertension, cardiac arrhythmias, myocardial infarction, and stroke in Pb exposed individuals [26][27][28][29][30], and hypertension, atherosclerosis, coronary artery disease, decreased heart rate variability, and increased all-cause CVD mortality in individuals exposed to DEHP and its metabolites [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have reported associations between phthalate exposure and an increased risk of all-cause and cardiovascular mortality, which has prompted a renewed interest in understanding the direct effect of DEHP on the heart(Trasande et al ., 2022; Zeng et al ., 2022). Identifying the consequences of clinical phthalate exposure on patient outcomes is inherently difficult, given the complexity of clinical care and the heterogenous nature of patient populations.…”
Section: Introductionmentioning
confidence: 99%